2019
DOI: 10.1016/j.bbmt.2018.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Practice Patterns of Physician Treatment for Pediatric Chronic Myelogenous Leukemia

Abstract: Chronic myelogenous leukemia (CML) is a rare disease in children for which pediatric evidence-based guidelines are lacking. We designed an anonymous survey for practicing pediatric oncologists and bone marrow transplantation (BMT) physicians to assess their willingness to recommend BMT for a patient with CML based on various clinical scenarios. A total of 274 physicians responded to the survey (13.4% response rate). Nearly all pediatric oncologists and BMT physicians recommended against BMT at time of diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…A survey of pediatric oncologists and HSCT physicians revealed that HSCT preference for pediatric CML is a minority, yet they were interested in a DMR-driven discontinuation trial [50]. Lifelong TKI treatment demands, especially from childhood to young adulthood, could lead to growth issues, potentially favoring HSCT.…”
Section: Children and Young Adultsmentioning
confidence: 99%
“…A survey of pediatric oncologists and HSCT physicians revealed that HSCT preference for pediatric CML is a minority, yet they were interested in a DMR-driven discontinuation trial [50]. Lifelong TKI treatment demands, especially from childhood to young adulthood, could lead to growth issues, potentially favoring HSCT.…”
Section: Children and Young Adultsmentioning
confidence: 99%
“…A recent comprehensive survey of 247 US-based pediatric hematologists' attitude towards an optimal treatment algorithm suggest that most do not support the use of allo-SCT for first-line therapy, and about 40% support it if suitable donor was available. 35 However, the vast majority support the use of allo-SCT following 2 lines of TKI therapy.…”
Section: Clinical and Treatment Issues In Pediatric Mpnsmentioning
confidence: 99%
“…Allo‐SCT should also be offered to CML patients who acquire the T315I mutation in BCR‐ABL1 , since the third generation TKI, ponatinib, is not currently licensed for children and adolescents. A recent comprehensive survey of 247 US‐based pediatric hematologists’ attitude towards an optimal treatment algorithm suggest that most do not support the use of allo‐SCT for first‐line therapy, and about 40% support it if suitable donor was available 35 . However, the vast majority support the use of allo‐SCT following 2 lines of TKI therapy.…”
Section: Clinical and Treatment Issues In Pediatric Mpnsmentioning
confidence: 99%
“…A survey was performed on a physician's idea about bone marrow transplant for CML detection among children, in the north of America. In this survey, 274 physicians have participated; about 7.8% of participants have recommended the bone marrow transplant for CML detection among children) Andolina et al, 2019(. Data mining methods have been used for different types of data related to patients with CML to detect potential targets (Benard, Gentles, Köhnke, Majeti, & Thomas, 2019).…”
Section: Introductionmentioning
confidence: 99%